2018
DOI: 10.3390/ijms19113316
|View full text |Cite
|
Sign up to set email alerts
|

The 2β Splice Variation Alters the Structure and Function of the Stromal Interaction Molecule Coiled-Coil Domains

Abstract: Stromal interaction molecule (STIM)-1 and -2 regulate agonist-induced and basal cytosolic calcium (Ca2+) levels after oligomerization and translocation to endoplasmic reticulum (ER)-plasma membrane (PM) junctions. At these junctions, the STIM cytosolic coiled-coil (CC) domains couple to PM Orai1 proteins and gate these Ca2+ release-activated Ca2+ (CRAC) channels, which facilitate store-operated Ca2+ entry (SOCE). Unlike STIM1 and STIM2, which are SOCE activators, the STIM2β splice variant contains an 8-residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Taken together, heterodimerization of STIM2.1 with STIM1 or STIM2.2 is likely responsible for the inhibitory effect of STIM2.1, as it has been shown that both CC2 helices are required to form the pocket that binds two Orai1 C-terminal helices [54]. Structural changes in one CC2 helix could thus collapse the whole Orai1 C-terminal helix-binding pocket [107]. However, it remains to be verified whether STIM2.1 inhibition is passive or active and whether there is more than one effect.…”
Section: Stim22 Isoformsmentioning
confidence: 98%
See 2 more Smart Citations
“…Taken together, heterodimerization of STIM2.1 with STIM1 or STIM2.2 is likely responsible for the inhibitory effect of STIM2.1, as it has been shown that both CC2 helices are required to form the pocket that binds two Orai1 C-terminal helices [54]. Structural changes in one CC2 helix could thus collapse the whole Orai1 C-terminal helix-binding pocket [107]. However, it remains to be verified whether STIM2.1 inhibition is passive or active and whether there is more than one effect.…”
Section: Stim22 Isoformsmentioning
confidence: 98%
“…Recent results from structural characterization studies on the Orai-activating small fragment (OASF, Figure 1) level have revealed a decisive impact of the STIM2.1 insert [107]. While not inducing a global conformational change, VAASYLIQ in the CC2 domain reduces the overall α-helicity of OASF, which exerts a destabilizing effect.…”
Section: Stim22 Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOCE is primarily driven by the formation and gating of Ca 2+ release-activated Ca 2+ (CRAC) channels composed of Orai1 subunits on the plasma membrane. The activation of these CRAC channels is mediated by stromal interaction molecule-1 and -2 (STIM1/2) which function as ER luminal Ca 2+ sensors that directly couple to Orai1 subunits and mediate gating of the channel after detecting decreases in ER Ca 2+ levels [12,13,14,15,16]. Ultimately, the increased cytosolic Ca 2+ mediated by SOCE not only signals downstream processes, but also replenishes the ER Ca 2+ stores via the action of the sarcoplasmic/endoplasmic Ca 2+ ATPase (SERCA) pumps [17].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing of STIM2 inserts 8 residues into the CC2 of CAD/ SOAR, transforming STIM2 from an activator into an inhibitor of Orai1 [49,50]. Biochemical studies thus far show that the insert reduces the helicity and enhances the exposed hydrophobicity of CAD/SOAR, which may underlie its inhibitory action [51]. Redox regulation of Orai1 has been traced to oxidation of C195 at the extracellular end of TM3 [52], which has been proposed to hydrogen bond with S239 at the top of TM4 to prevent channel opening [53].…”
Section: Beyond Activation: Negative Regulation Of Socementioning
confidence: 99%